2015
DOI: 10.1038/ncomms10099
|View full text |Cite
|
Sign up to set email alerts
|

DARPP-32 interaction with adducin may mediate rapid environmental effects on striatal neurons

Abstract: Environmental enrichment has multiple effects on behaviour, including modification of responses to psychostimulant drugs mediated by striatal neurons. However, the underlying molecular and cellular mechanisms are not known. Here we show that DARPP-32, a hub signalling protein in striatal neurons, interacts with adducins, which are cytoskeletal proteins that cap actin filaments' fast-growing ends and regulate synaptic stability. DARPP-32 binds to adducin MARCKS domain and this interaction is modulated by DARPP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Alternatively, adducins could function in activity-dependent barbed end capping as they cap the barbed end of actin filaments and cross-link them with the spectrin cytoskeleton [49]. β-adducin is localized to dendritic spines and mice lacking β-adducin display impaired synaptic plasticity, motor coordination and learning deficits [5053]. Modulation and specificity of capping activity amongst these various classes of barbed end capping proteins is likely specified by binding partners, differential affinity for barbed ends, other actin-regulatory domains within the protein (such as bundling or severing) and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, adducins could function in activity-dependent barbed end capping as they cap the barbed end of actin filaments and cross-link them with the spectrin cytoskeleton [49]. β-adducin is localized to dendritic spines and mice lacking β-adducin display impaired synaptic plasticity, motor coordination and learning deficits [5053]. Modulation and specificity of capping activity amongst these various classes of barbed end capping proteins is likely specified by binding partners, differential affinity for barbed ends, other actin-regulatory domains within the protein (such as bundling or severing) and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Adducins are actin‐capping proteins that stabilize the cortical cytoskeleton and regulate synaptic stability (Engmann et al . ). In particular, β‐adducin is essential for the stability of dendritic spines and is involved in learning and memory processes through the regulation of actin‐ and spectrin‐based synapse formation (Bednarek and Caroni ; Pielage et al .…”
mentioning
confidence: 97%
“…C-E, immunohistochemical analysis of P-ERK in the dorsal striatum (C), NAc core (D), and NAc shell (E) from wild type and S97A mice. mechanism (10) and also by decreased binding to adducin, which is a cytoplasmic partner (11). However, in contrast to the nuclear accumulation of phospho-Thr-34 DARPP-32 observed after activation of PKA signaling, following glutamate signaling, dephospho-Thr-34 DARPP-32 accumulates in the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent studies revealed that Ser-97 phosphorylation of DARPP-32 acts in conjunction with a nuclear export signal to facilitate export of DARPP-32 from the nucleus (10). In addition, phosphorylation of Ser-97 increases the interaction of DARPP-32 with adducin, a protein associated with cortical actin-spectrin cytoskeleton (11). The results from the current study suggest that glutamate can act via AMPA and/or NMDA receptors to induce the dephosphorylation of DARPP-32 at Ser-97 by PP2A/PR72.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation